Differential Diagnosis of Polyhydramnios in a Patient with Gestational Diabetes and Structurally Abnormal Fetus - GICA, Nicolae (Maedica (Bucur), 2019)
ABSTRACT Polyhydramnios is frequently seen in patients with diabetes in pregnancy, as well as in cases of fetal malformations. The aim of our paper is to present a rare case of a fetus with anomalies of the precordial veins (absent ductus venosus, intracardiac drainage of the umbilical vein, persistent left superior vena cava) and upper intestinal tract obstruction. The mother developed gestational diabetes and polyhydramnios, in this case. The 29-year-old patient was admitted to our hospital at 35 weeks of gestation with ruptured membranes. Cesarean section was performed. A live baby boy, 2400 g, with multiple congenital abnormalities (including esophageal atresia) was delivered. Our case illustrates the diagnostic approach to polyhydramnios and the difficulty to prenatally diagnose esophageal atresia, in the context of a fetus with multiple malformations.